2023
DOI: 10.3389/fbioe.2023.1224945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of citrate-stabilized gold and silver nanoparticles on some safety parameters of Porphyridium cruentum biomass

Abstract: Introduction: Our research raises the question of how realistic and safe it is to use gold and silver nanoparticles in biotechnologies to grow microalgae, which will later be used to obtain valuable products. To this purpose, it was necessary to assess the influence of 10 and 20 nm Au and Ag nanoparticles stabilized in citrate on the growth of microalga Porphyridium cruentum in a closed cultivation system, as well as some safety parameters of biomass quality obtained under experimental conditions.Methods: Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The remarkable bioavailability of nanoparticles supports the idea that they could represent more efficient sources of trace elements compared to their macroscopic forms, thereby contributing to improve vital functions [16]. Silver nanoparticles (AgNPs) are among the most actively used in various fields, such as the food industry, agriculture, textile industry, medical industry, and phycobiotechnologies, including for the valorization of Porphyridium purpureum biomass [8,11,[17][18][19]. Thus, AgNPs are used as stimulants for biosynthetic activity, primarily lipids, the content of which can increase in microalgal biomass by 3-8 times [15,18].…”
Section: Quantity Of P Purpureum Cnmn-ar-02 Biomass Produced Under Cu...mentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable bioavailability of nanoparticles supports the idea that they could represent more efficient sources of trace elements compared to their macroscopic forms, thereby contributing to improve vital functions [16]. Silver nanoparticles (AgNPs) are among the most actively used in various fields, such as the food industry, agriculture, textile industry, medical industry, and phycobiotechnologies, including for the valorization of Porphyridium purpureum biomass [8,11,[17][18][19]. Thus, AgNPs are used as stimulants for biosynthetic activity, primarily lipids, the content of which can increase in microalgal biomass by 3-8 times [15,18].…”
Section: Quantity Of P Purpureum Cnmn-ar-02 Biomass Produced Under Cu...mentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) are among the most actively used in various fields, such as the food industry, agriculture, textile industry, medical industry, and phycobiotechnologies, including for the valorization of Porphyridium purpureum biomass [8,11,[17][18][19]. Thus, AgNPs are used as stimulants for biosynthetic activity, primarily lipids, the content of which can increase in microalgal biomass by 3-8 times [15,18]. Studies have shown the stimulating action of AgNPs on other biosynthetic processes such as carbohydrate production [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation